A Sense for Training in Systems Engineering - Parra-Valencia, Jorge Andrick (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The purpose of this article is to present a meaning for the formation of the Systems Engineering Program of the Autonomous University of Bucaramanga, from its Institutional Educational Project and from the origins and foundations of systems engineering. Based on this presentation, some general competencies of the program are proposed. The article offers this reflection exercise as a way to rethink training in systems engineering, from the intention of respecting the context from which this interdisciplinary engineering intervention is carried out.